KAJIAN EMISI CO2 DARI PEMANFAATAN ENERGI RUMAH TANGGA DI KELURAHAN CANDI KOTA SEMARANG - Subkhan, Akhmad; Setyowati, Dewi Liesnoor; Setyaningsih, Wahyu (Geo-Image, 2017)
The imbalance between the settlement area (53.27%) and the RTH (9.73%) in the Candi Village gave the GHG potential from high CO2. The extent of residential land affects the high emissions from energy consumption due to the large number of households, while at least green space causes the low absorption of CO2. The research objectives were: (1) analyzed carbon dioxide emissions by home energy consumption and (2) analyzed the absorption of carbon dioxide by trees from household energy consumption. The research population is household and tree. Sampling technique for household is purposive sampling and proportional random sampling. While the trees with a thorough enumeration technique. Variabel research consists of (1) emissions of carbon dioxide from energy utilization and (2) the absorption of emissions by trees. Methods of data collection are observation, interview, and documentation, and data analysis using formula calculation, comparative analysis, and descriptive percentage analysis. The results stated that total emissions from gasoline consumption amounted to 881.10 tons/year, LPG of 976,61 tons/year, and electricity 3.377,20 tons/year). The total emission is 5.243,48 ton/year, while total absorption is 1.072,45 ton/year, so there are 4.17102 ton/year of emission that can not be absorbed.